Gambaran Pengetahuan, Sikap, Ketersediaan APD dan Kebijakan Dengan Penggunaan APD Pada Paramedis di Rumah Sakit Kabupaten Aceh Utara - Ufairah Ariqah Heru; Juwita Sahputri; Maulana Ikhsan (PT FORMOSA CENDEKIA GLOBAL, 2022)
Personal Protective Equipment (PPE) is a tool used to protect oneself or the body against the dangers of accidents in the workplace which can technically reduce the severity of accidents that occur. The purpose of this study was to describe the knowledge, attitudes, availability of PPE and policies with the use of PPE for paramedics in the inpatient ward of the hospital. This research is a descriptive analytic study using a cross sectional approach. The sampling used in this study was simple random sampling with a total of 137 nurses and midwives who had met the inclusion and exclusion criteria. The results of the univariate analysis showed good knowledge of 88.3%, good attitude 90.5%, PPE not available 78.1%, policy 96.4%, not using PPE 78.1%. The conclusion of this study is that knowledge and attitudes are in the good category, PPE is not available, there is a policy, and does not use PPE.